Commentary on "Constraints on the Equations of State of stiff anisotropic minerals: rutile, and the implications for rutile elastic barometry" [Miner. Mag. 83 (2019) pp. 339–347]. (April 2020) - Angel, Ross J.; Alvaro, Matteo; Schmid-Beurmann, Peter; Kroll, Herbert
Abstract: The conclusion of Zaffiro et al. (2019; Constraints on the Equations of State of stiff anisotropic minerals: rutile, and the implications for rutile elastic barometry. Mineralogical Magazine, 83, 339–347) that the Mie–Grüneisen–Debye (MGD) Equation of State (EoS) cannot fit the available data for rutile is shown to be incorrect, even though rutile exhibits significant anisotropic thermal pressure which invalidates the quasi-harmonic approximation used as the basis for the MGD EoS. The refined parameters for the MGD EoS of rutile are: K TR 0 = 205.05(25) GPa, $K_{TR0}^{′} $ = 7.2(5), θ D = 399(20) K, γ0 = 1.40(2) and q = 1.5(7). This EoS predicts volumes, bulk moduli and volume thermal expansion coefficients for rutile at metamorphic conditions that are statistically indistinguishable from those predicted by the 'isothermal' type of EoS reported previously.